Loving Gardens, Loving the Gardener? 'Solitude' in Andrew Marvell's 'The Garden'. Issue 2 (11th October 2018) - Seymour, Laura
Abstract : In 'The Garden', Andrew Marvell devotes a lot of time to extolling the virtues of the solitude he experiences in the garden of the title. Despite Marvell's insistence that he prefers solitude to 'society', at the end of the poem his attention comes to rest approvingly on a human figure: the Gardener. Reading 'The Garden' alongside 'Damon the Mower', this article suggests that Marvell's sensually-charged engagement with the plants, trees, and fruits in 'The Garden' can be interpreted as a means of accessing and loving the Gardener himself. On one reading of 'Damon the Mower', the narrator caresses Damon through the landscape. Tracking similar themes in 'The Garden' suggests that something similar may be occurring in this poem, too.